Enfoques, modelos y líneas emergentes en educación patrimonial: hacia una educación de calidad a través de las artes - Sofía Victoria Marín-Cepeda; Carmen Gómez-Redondo (Universidade Federal do Norte do Tocantins, 2021)
The latest paradigm shifts in heritage didactics focuses to the need of participation and subjective experience in educational designs and, during the last years, several researches have arisen around plastic and visual education and its use as tools for mediation between people and heritage. The aim of this article is to analyze the academic production on heritage education through PVT (plastic and visual techniques) in journals of the Web of Science Core Collection (WOS) databases in the last 10 years (2010-2020). Bibliographic searches and analyses were performed through high-impact indicator analysis, making microspecialized searches in WOS. Bibliometric techniques were applied to identify the main lines of research, topics and PVT. The data were processed with VOSviewer and an in-depth qualitative analysis. In relation to the results, four approaches have been observed: a first approach focused on the communication of heritage, a second one focused on the use of plastic techniques as a form of expression, a third one focused on the use of ICT as an educational tool, and a fourth one focused on the experiential relationship with the environment.